2010
DOI: 10.4253/wjge.v2.i7.252
|View full text |Cite
|
Sign up to set email alerts
|

Esophagitis dissecans superficialis and autoimmune bullous dermatoses: A review

Abstract: Esophagitis dissecans superficialis (EDS) is a rare and severe endoscopic finding characterized by sloughing of large fragments of esophageal mucosal lining. Although EDS has been reported in association with serious illnesses and certain medications, the pathophysiological association of autoimmune bullous dermatoses with EDS has gained remarkable attention. Among these dermatoses, pemphigus vulgaris and pemphigoid frequently present with various types of esophageal involvement including EDS. We review the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 39 publications
1
48
0
7
Order By: Relevance
“…Offending agents should be discontinued. Currently, there are no published surveillance guidelines [7, 10]. …”
Section: Discussionmentioning
confidence: 99%
“…Offending agents should be discontinued. Currently, there are no published surveillance guidelines [7, 10]. …”
Section: Discussionmentioning
confidence: 99%
“…2 Esophageal involvement in PV may be more prevalent than previously recognized. 4 Absence of cutaneous or oral pharyngeal lesions and immunofluorescence can assist in ruling out PV.…”
mentioning
confidence: 94%
“…1,2 Although no one specific etiology has been identified, a recent study found that patients with EDS were older and were more likely to be chronically debilitated, to have died since biopsy, and to be taking 5 or more medications when compared with the control population. 3 They were more likely to have hypertension and heart conditions such as valvular disease, arrhythmia, and congestive heart failure.…”
mentioning
confidence: 97%
“…Few case reports have suggested strong association with desquamating esophageal disorders, in particular Pemphigus Vulgaris [2,3]. Rao at el evaluated 42 patients with vesciculobullous dermatosis and found esophageal involvement in 27 patients (67%) and classical appearance of EDS in 2 patients (5%) [4].…”
Section: Discussionmentioning
confidence: 99%